The level of homophobia in academic personnel at a university in istanbul and its affecting factors [İstanbul’da bir üniversitede akademik personelin homofobi düzeyi ve etkileyen faktörler] - (:unkn) unknown (Nobelmedicus, 2020)
Objective: This descriptive study aimed to evaluate a university academic staff with factors affecting attitudes towards homosexuals. Material and Method: A questionnaire consisting of Hudson and Ricketts Homophobia Questionnaire, was applied to participants between February 15 and April 15, 2016. Questionnaires were distributed to a total of 200 academic staff working in a university in İstanbul and 132 people agreed to participate. Results: The present results indicate clearly that women and young people have a more positive attitude towards homosexuality. The homophobia level of homosexual acquaintances was significantly lower than that of those without homosexual acquaintances. As participants degree of familiarity with homosexuals increased, the level of homophobia was found to be significantly lower. The level of homophobia of those who were aware of a homosexual relative was significantly lower. It was found that those who were familiar with gay individuals considered homosexuality more as sexual orientation. Conclusion: The findings indicate that culture may affect the attitudes toward homosexuality. Attitudes towards homosexuality can be altered via education and information while improvement of social interaction is possible with communication and acquaintance. It can be concluded that scientific knowledge, communication and social alignment are important topics for a healthy society. © 2020, Nobelmedicus. All rights reserved.
Keywords: Academic personnel; Homosexuality; Stigma